The Effects of Irisin Hormone and the FNDC5 Gene on Brain Functions and Exercise: A Systematic Review - Özgür Eken (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The aim of this systematic review was to regroup all systematic reviews, non-systematic reviews and all original articles between 2017 and 2021 (including June) into one convenient publication that would facilitate the theoretical and applied scientific investigations directed on the efficacy of exercise and brain function on irisin hormone and FNDC5 gene. Evidence Acquisition: The systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. A computer-based systematic search was conducted in July 2021 through Google Scholar, Pub Med, and Science Direct databases. The reliability of the systematic research was ensured by completely repeating the article selection process by a second author. Evidence Synthesis: Twenty-six articles that met the criteria out of 279 articles obtained specifically for keywords were included in the review. Results show that together with different types of exercise, irisin and FNDC5 may be new biomarkers that should be considered in reducing neurodegenerative disorders and improving neuromuscular and brain functions. Conclusion: Based on the articles included in this review, increasing the number of studies examining the potential of short and long-term exercises to stimulate irisin and FNDC5 gene in the future may help to understand the effects of exercise on Irisin and FNDC5 mediated brain functions.